Four new genera of Schizopteridae (Hemiptera: Heteroptera) from the Afrotropical and Neotropical regions - Weirauch, Christiane; Knyshov, Alexander; Hoey-Chamberlain, Rochelle (Zootaxa, 2020)
Despite a recent surge of taxonomic work on the dipsocoromorphan family Schizopteridae, new genus-level taxa remain to be documented and described. The curation of Malaise and Yellow Pan Trap sample residues from Central and South America and Cameroon resulted in the discovery of five undescribed species that based on combined molecular and morphological phylogenetic analyses represent four phylogenetically isolated lineages within non-hypselosomatine Schizopteridae. To accommodate these new species, we here describe the four new genera Caucanannus gen. n. (Colombia, Ecuador, and Brazil) with Caucanannus perplexus sp. n. and Caucanannus novissimis sp. n.; Kamakonocoris gen. n. (Cameroon) with Kamakonocoris carinata sp. n.; Perittonannus gen. n. (Costa Rica) with Perittonannus antiquus sp. n.; and Rimanannus gen. n. (Cameroon) with Rimanannus camerunensis sp. n. The four genera are characterized by distinctive wing venation and male and female genitalic features. We provide habitus photographs and document morphological details using digital macrophotography as well as light compound microscopic and scanning electron microscopic images. Maps and measurements are also included.